Urban-rural differences in male cancer incidence and mortality in the Umbria region of Italy (Italian Journal of Public Health, 2007)
Background: The aim of this study is to verify the existence of different rates of cancer incidence and mortality in males in the urban and rural populations of Umbria and to formulate hypotheses as to why this occurs. Methods: Directly age-adjusted incidence rates (AAIR) and age-adjusted death rates (AADR) were calculated for 1998-2002 and the expected number of rural cases (standardized incidence ratios-SIRs and standardized mortality ratios-SMRs) was determined by indirect standardization using urban incidence and mortality. Results: Urban zones have higher AAIR’s for the most common cancer sites. Significantly lower SIRs, in rural areas, were shown for skin melanoma, prostate and bladder cancers and a significantly lower SIR was also determined for the combination of all cancer sites. Lower AADRs in rural areas were demonstrated for the most common cancer sites and significant low SMRs were shown for lung cancer and skin melanoma. Prostate cancer incidence is significantly higher in urban areas whereas the mortality rate is slightly higher in rural municipalities probably due to the effects of the opportunistic screening widely available in Umbria, particularly in zones near diagnostic services. A very similar pattern was found for urinary bladder cancer; this could be related to the association between prostate and bladder cancer sites. Both incidence and mortality from melanoma are significantly lower in rural areas, this may be due to the difficulty in accessing diagnostic services or/and to different occupational exposure patterns. Conclusion: It would appear in Umbria that differences in health services utilization continue to exist. In particular, our results are compatible with a lower diffusion of preventive activities for prostate cancer and skin melanoma in rural areas.
Keywords: Urban-rural differences; cancer incidence; cancer mortality